Entrepreneurial Leadership Towards Innovative Work Behavior in MSMEs Through Creative Self Efficacy as a Mediation - Leozarus Deo; Roby Sambung; Olivia Ony Panjaitan (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
Objective – This study aims to provide an empirical explanation of the Effect of Entrepreneurial Leadership on Innovative Work Behavior in MSMEs engaged in culinary business in Palangka Raya City through Creative Self Efficacy as a Mediating Variable.Design/Methodology/Approach – The analysis method used in this research is descriptive method with quantitative approach. The population and sample in this study were employees who worked for MSMEs engaged in the culinary sector who had more than 5 (five) employees in Palangka Raya City, totaling 140 people. IBM SPSS Statistical 25 and SmartPLS 3.0 were used to conduct Likert scale analysis on the data collected.Findings – The results showed that entrepreneurial leadership has a significant effect on innovative work behavior and creative self-efficacy partially mediates between entrepreneurial leadership and innovative work behavior on MSMEs employees in the culinary business sector in Palangka Raya City.Implications – Entrepreneurial leadership directly through creative self efficacy has a positive influence on innovative work behavior of MSMEs. Business actors and employees can maintain entrepreneurial leadership and maintain creative self efficacy to be able to increase innovative work behavior in culinary MSMEs businesses in Palangka Raya City.